DNA topology in chromatin is defined by nucleosome spacing - Nikitina, Tatiana (Sci Adv, 2017)
In eukaryotic nucleosomes, DNA makes ~1.7 superhelical turns around histone octamer. However, there is a long-standing discrepancy between the nucleosome core structure determined by x-ray crystallography and measurements of DNA topology in circular minichromosomes, indicating that there is only ~1.0 superhelical turn per nucleosome. Although several theoretical assumptions were put forward to explain this paradox by conformational variability of the nucleosome linker, none was tested experimentally. We analyzed topological properties of DNA in circular nucleosome arrays with precisely positioned nucleosomes. Using topological electrophoretic assays and electron microscopy, we demonstrate that the DNA linking number per nucleosome strongly depends on the nucleosome spacing and varies from −1.4 to −0.9. For the predominant {10n + 5} class of nucleosome repeats found in native chromatin, our results are consistent with the DNA topology observed earlier. Thus, we reconcile the topological properties of nucleosome arrays with nucleosome core structure and provide a simple explanation for the DNA topology in native chromatin with variable DNA linker length. Topological polymorphism of the chromatin fibers described here may reflect a more general tendency of chromosomal domains containing active or repressed genes to acquire different nucleosome spacing to retain topologically distinct higher-order structures.